Sustainable diet within global food system: from people to planet to people - Mai Magdy (Multidisciplinary Adaptive Climate Insights, 2024)
Sustainability in global food system is an urgent necessity, it is a highly debatable topic; food scientists, local farmers, food manufacturers, private sector and governments regularly gather for decisive decisions to be dictated. However, one or more party usually oppose, here is the major conundrum of Sustainable Diet within Global food system. This paper deals with Sustainable Diet Notions, tackling food waste and agro-waste, understanding different supply chains in the food system and how circular economy should be effectively applied. All are introduced with evidence-based innovative ideas-from multidisciplinary and circular-economy perspectives-to a. Reduce carbon footprint, b. Save resources and huge economic burden of waste control, c. Provide an idea for a new possible merging market based on eco-friendly and planet saving technology, d. Significantly reduce food waste, e. Significantly reduce food insecurity, hunger and hidden hunger.   Received: 15 September 2024 Accepted: 03 November 2024 Published: 17 November 2024